Spatial Analysis of Global Variability in Covid-19 Burden - Miller LE; Bhattacharyya R; Miller AL (Dove Medical Press, 2020)
Larry E Miller, Ruemon Bhattacharyya, Anna L Miller Department of Biostatistics, Miller Scientific, Johnson City, TN, USACorrespondence: Larry E MillerMiller Scientific, Johnson City, TN, USATel +1 828-450-1895Email larry@millerscientific.comBackground: Since the first occurrence of coronavirus disease 2019 (Covid-19), a number of online tools have become available to assist with tracking Covid-19 prevalence. Yet we are unaware of resources that provide country-specific Covid-19 incidence data.Methods: We undertook a descriptive analysis of the global impact of Covid-19 using data reported on March 17, 2020. The prevalence of Covid-19 cases, fatalities attributed to Covid-19, and the case fatality rate for each of the 238 countries were accessed from the World Health Organization global Covid-19 tracking site, and we additionally calculated Covid-19 incidence based on country-specific population data. We determined the country-specific point prevalence and incidence of Covid-19 and associated deaths while using geocoded data to display their spatial distribution with geographic heat maps.Results: The analysis included 193,197 Covid-19 cases and 7859 associated deaths. The point prevalence was highest in China (80,881), Italy (31,506), Iran (16,169), and Spain (11,312); no other country reported more than 10,000 cases. The incidence (per million population) was highest in San Marino (3389) followed by Iceland (645) and Italy (521); no other country had an incidence above 400 per million population.Conclusion: Countries with a high Covid-19 prevalence may not have a high incidence, and vice versa. Public health agencies that provide real-time infection tracking tools should report country-specific Covid-19 incidence metrics, in addition to prevalence data.Keywords: coronavirus, Covid-19, incidence, prevalence